STUDI EVALUASI INSTALASI PENGOLAHAN AIR BERSIH UNTUK KEBUTUHAN DOMESTIK DAN NON DOMESTIK (STUDI KASUS PERUSAHAAN TEKSTIL BAWEN KABUPATEN SEMARANG) - Hardyanti, Nurandani; Fitri, Nurmeta Diana (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2006)
Water  was  the  fundamental  needs  for  industrial  in  every  production  process  and  all  the activities. Apac  Inti  Corpora  company  was  the  textile  industrial  with  production  process  are spinning  and weaving.  It  usually  required  water  with  high  quality  such  as  lowest  pH  and hardness. They needed high quality water by water treatment plant. They treated ground water that contained manganese and iron to fulfill domestic needs by aerasi and filtrasi with filter sand. They  treated  water  from  Bade  river  and Sarana  Tirta  Ungaran  to  fulfill  non  domestic  needs. Water  from  Bade  river  contained  highest colour  and  turbidity  and  processed  with  screening, coagulation, flokulalation, sedimentation and filtration. To eliminate content of hardness, these water continued to treat by  softener unit. Softener  unit will degrade kesadahan less than 5 ppm CaCO 3 . Quality of treated water has been fulfilled Permenkes RI No.907/MENKES/SK/VII/2002, except colour content from Bade river.